PENGARUH KESIBUKAN ORANG TUA TERHADAP POLA BELAJAR ANAK USIA 7-10 TAHUN DI RW 04 KARANGANYAR JEMBER - Said Mardjanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2014)
Academic achievement is a reflection of the learning ability of students in participating schools and can be used as one indicator of the success of the learning process. Knowing the purpose of this study was the effect of the busyness of parents of the learning patterns of children aged 7-10 years in RW 04 Karanganyar. Design research in this study using quantitative methods. Sampling was done by purposive sampling technique, the number of samples used is the number of 37 respondents. The results showed 91.8% not including busy parents, 8.1% is a pretty busy parents, 91.8% had a pattern of good study, 8.1% have sufficient learning patterns, based on hypothesis testing using the Spearman Rank in getting Significance = 0.007 (P <0.05) and ρ = 0.433 (ρ count> ρ table) thus proved the influence of the busyness of parents with a child's learning pattern. For parents to continue to support both psychologically and materially, psychological support is extremely important that this is because the child feels himself noted, this kind of support has a direct impact on children so that children are more eager to learn